Helper T cells (CD3+/CD4+) within the autologous peripheral blood stem cell graft positively correlate with event free survival of multiple myeloma patients - Schmidmaier, R.; Oversohl, N.; Schnabel, B.; Straka, C.; Emmerich, B. (Experimental Oncology, 2008)
The microenvironment in the bone marrow — including lymphocytes — is part of the pathophysiology of multiple myeloma (MM). High dose chemotherapy followed by autologous stem cell transplantation is standard of care for younger patients. Aim: To determine the influence of reinfused lymphocyte subsets on event free survival (EFS) and overall survival (OS). Methods: In peripheral blood (PB) and aphaeresis products (AP) of 41 MM patients lymphocyte subsets were determined by flow cytometry and were correlated with clinical outcome. Results: PB lymphocyte subsets did not influence EFS or OS. Residual plasma cells in the AP were not correlated with poor outcome, whereas a high percentage of B cells (CD19+) showed a trend towards reduced EFS (P = 0.051). A high amount of CD4 cells and an increased CD4/CD8 ratio were significantly associated with prolonged EFS. In contrast, high percentage of HLA-DR positive lymphocytes showed negative impact on EFS and OS (P = 0.03 and 0.02, respectively). Conclusion: Obtained data suggest the non-activated (HLA-DR negative) helper CD4+ T cells in the AP to be tumour protective.